2008
DOI: 10.1292/jvms.70.423
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an H1N2 Swine Influenza Virus Isolated in Miyazaki, Japan, in 2006

Abstract: ABSTRACT. Swine influenza virus (SIV) was isolated from a farm in Miyazaki Prefecture in Japan in July 2006. An isolate was genetically subtyped as H1N2 and was designated A/swine/Miyazaki/1/2006 (H1N2). The nucleotide sequences of all eight viral RNA segments were determined, and then phylogenetic analysis was performed using the neighbor-joining method. All segments were shown to be closely related to those of Japanese SIV H1N2 isolates, which have been circulating since the 1980s. The results indicate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Phylogenetic analysis of HA gene sequences of both viruses obtained by direct sequencing of the nasal swabs revealed that they belonged to the classical swine H1 lineage (data not shown). N1 and other internal genes of Rat101942 resided in the Eurasian avian-like swine lineage (data not shown), as did previously characterized Thai H1N1 isolates (Takemae et al, 2008).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Phylogenetic analysis of HA gene sequences of both viruses obtained by direct sequencing of the nasal swabs revealed that they belonged to the classical swine H1 lineage (data not shown). N1 and other internal genes of Rat101942 resided in the Eurasian avian-like swine lineage (data not shown), as did previously characterized Thai H1N1 isolates (Takemae et al, 2008).…”
Section: Resultssupporting
confidence: 82%
“…The inoculated cells were incubated for more than 48 h at 37 uC in 5 % CO 2 until the cytopathogenic effect appeared. Haemagglutinating agents arising from the same swab in both an embryonated egg and MDCK cells were identified as H1N1 by the PCR method using specific primers designed in a previous study (Takemae et al, 2008). They were designated A/swine/Ratchaburi/NIAH101942/2008 (H1N1) (Rat101942).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations